Saudade e diáspora na rádio: “O estranho caso do programa de rádio português quase líder de audiência no Brasil” - Alves, Teresa Costa (2014)
Portugal and Brazil share more than 500 years of its history. Under the aegis of of a common language, Portuguese culture has some manifestations in Brazilian radio. In most Brazilian radio stations belonging to large media business groups, cultural contents of Portuguese origin are not among the strategic priorities of the most heard stations. However, there is an exception in Sao Paulo, on radio Capital: the program "Portugal, a saudade e você", deputy leader of audience in its time slot, only losing to the Globo radio on Sunday hours, between 8am and 9pm. In what ways is structured the program? How is it received in the context of the Portuguese diaspora in Brazil? What are the possible reasons for the ratings success of this program? These and other issues will be discussed and future research lines presented.